2007
DOI: 10.1111/j.1610-0387.2007.06177.x
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic treatment of cutaneous leishmaniasis

Abstract: Leishmaniasis is a widespread arthropod-borne protozoan zoonosis caused by more than 21 Leishmania species. Vectors are sandflies of different genera. The disease is classified into "Old World" versus "New World" leishmaniasis and further subclassified in cutaneous, mucocutaneous and visceral forms. Most therapeutic approaches are not evidence-based. We report a patient with facial cutaneous Leishmania tropica infection which proved to be resistant to various therapeutic regimes. Excellent results were achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 12 publications
0
26
0
1
Order By: Relevance
“…PDT of 75 J/cm 2 red light performed 12 weeks also showed good results 102. Leishmania tropica infection which proved to be resistant to various therapeutic regimes was effectively treated by PDT 103. It is also more effective than topical paromomycin and methylbenzethonium chloride used for cutaneous Leishmaniasis 104.…”
Section: Pdt Of Leishmaniasismentioning
confidence: 99%
“…PDT of 75 J/cm 2 red light performed 12 weeks also showed good results 102. Leishmania tropica infection which proved to be resistant to various therapeutic regimes was effectively treated by PDT 103. It is also more effective than topical paromomycin and methylbenzethonium chloride used for cutaneous Leishmaniasis 104.…”
Section: Pdt Of Leishmaniasismentioning
confidence: 99%
“…Various case reports and series have documented successful treatment of cutaneous leishmaniasis using PDT. Studies have also shown PDT to be effective in the treatment of antibiotic-resistant cutaneous leishmaniasis, further strengthened by another study comparing the efficacy of PDT versus paromomycin or methylbenzethonium chloride 148151. Individual cases demonstrating successful treatment using MAL-PDT include an 8-year-old Italian girl and an Austrian patient infected with Leishmania major 91,152.…”
Section: Pdt In Microbial Diseasesmentioning
confidence: 99%
“…PDT of 75 J/cm 2 red light performed 12 weeks also showed good results (135). Sohl, Kauer et al reported that excellent results were achieved with PDT on a patient with facial cutaneous Leishmania tropica infection which proved to be resistant to various therapeutic regimes (136). PDT was showed to be more effective than topical paromomycin and methylbenzethonium chloride in the therapy of cutaneous leishmaniasis (137).…”
Section: Pdt For Clinical Infectious Diseasementioning
confidence: 99%